80.2k views
0 votes
5×67=

a. (67×10)÷2
b. (67x2)+(67×2)
c. (6 ×7)×5
d.(5×6)+(5×7)​

1 Answer

6 votes

Answer:

a).

= (67×10)÷2

= 670 ÷ 2

= 335

Explanation:

a).

= (67×10)÷2

= 670 ÷ 2

= 335

So, 5×67 = (67×10)÷2

=> 335 = 335

b).

= (67x2)+(67×2)

= 134 × 134

= 268

So, 5×67 ≠ (67x2)+(67×2)

=> 268 ≠ 335

c).

= (6 ×7)×5

= 42 × 5

= 210

So, 5×67 ≠ (6×7)×5

=> 210 ≠ 335

d).

= (5×6)+(5×7)

= 30 + 35

= 65

So, 5×67 ≠ (5×6)+(5×7)

=> 65 ≠ 335

Hence, (a) is the correct answer.

User RafaSashi
by
5.0k points